2021
DOI: 10.21037/jtd-20-1819
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic vein harvesting

Abstract: Coronary artery bypass grafting is the most common cardiac surgical procedure performed worldwide and the long saphenous vein the most common conduit for this. When performed as an open vein harvest (OVH), the incision on each leg can be up to 85cm long, making it the longest incision of any routine procedure. This confers a high degree of morbidity to the procedure. Endoscopic vein harvest (EVH) methods were popularised over two decades ago, demonstrating significant benefits over OVH in terms of leg wound co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…16 A meta-analysis by Akowuah et al concluded that, in experienced hands, there was no increase in MACE or mortality in midterm and long-term follow-up. 17 The purpose of this study was to delineate the impact of vein morphology on the 15-year outcomes of EVH. This study was designed only to evaluate survival and MACE outcomes and not graft patency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 A meta-analysis by Akowuah et al concluded that, in experienced hands, there was no increase in MACE or mortality in midterm and long-term follow-up. 17 The purpose of this study was to delineate the impact of vein morphology on the 15-year outcomes of EVH. This study was designed only to evaluate survival and MACE outcomes and not graft patency.…”
Section: Discussionmentioning
confidence: 99%
“…16 A meta-analysis by Akowuah et al concluded that, in experienced hands, there was no increase in MACE or mortality in midterm and long-term follow-up. 17…”
Section: Discussionmentioning
confidence: 99%
“…Although SVG preparation in CABG is an important step of the surgery, it is traditionally prepared with long incisions or bridged incisions [15]. When performed with the conventional surgical method, the incision in each leg can be up to 85 cm long, making it one of the longest incisions of any routine surgery [16]. Various complications can be seen in the incision area after SVG preparation, especially in patients with risk factors such as obesity (BMI> 30), diabetes mellitus, peripheral vascular disease and female patient.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic vein harvesting (EVH) consists of the dissection and the harvest of the graft, videoscopically guided, through small skin incisions. This method is thought to reduce the rate of wound-related complications [ 61 ]. Despite the potential benefit of this technique, in 2009, a subgroup analysis of the PREVENT trial demonstrated that EVH was associated with a significantly higher rate of failure compared to open harvesting at a 12- to 18-month follow-up.…”
Section: Surgical Techniquesmentioning
confidence: 99%